Investment, Resolution of Risk, and the Role of Affect - Frans van Winden; Michal Krawczyk; Astrid Hopfensitz (Tinbergen Institute, 2008)
This experimental study is concerned with the impact of the timing of the resolution of risk onpeople's willingness to take risks, with a special focus on the role of affect. While the importanceof anticipatory emotions has so far been only inferred from decisions regarding hypothetical choiceproblems, we had participants put their own money at risk in a real investment task. Moreover,emotions were explicitly measured, including anticipatory emotions experienced during the waitingperiod under delayed resolution (which involved two days). Affective traits and risk attitudes weremeasured through a web-based questionnaire before the experiment and participants' preferencesfor resolution timing, risk, and time were incentive compatibly measured during the experiment.Main findings are that delayed resolution can affect investment, that the effect depends on the riskinvolved, and that (among all the measures considered) only emotions can explain our results,albeit in ways that are not captured by existing models.
Keywords: C91; D81; G11; 330; Investment decision; delayed resolution of risk; emotions; experiment; Investition; Entscheidung bei Risiko; Emotion; Test